The effect of an environmental tax on the consumption of dairy and plant-based drinks : the case of Sweden - Törnqvist, Daniel (SLU/Dept. of Economics, 2022)
In the light of global greenhouse gases (GHG) mitigation targets, this study aims to investigate if a consumption-sided CO2e weighted tax scheme on dairy and plant-based drinks can shift consumption towards plant-based drinks and thereby lower GHG emissions. Using scanner data from a Swedish supermarket ICA Maxi Nacka located in Stockholm, Sweden, we construct a multistage Quadratic Almost Ideal Demand System (QUAIDS) to evaluate changes in demand due to the tax implementation. The results show that net GHG emissions are reduced by 4.27 percent where 100 percent of the reductions stem from reduced dairy consumption and 100 percent of the increases from increased plant-based drinks consumption. In the sensitivity analysis we exempt oat drinks from the taxation which marginally increased the demand resulting in increased net GHG reductions of 4.40 percent.